Remedying Copyright for Indigenous Australians: A Stolen Generations Perspective - Serventy, Elizabeth; Koutras, Nikos (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2026)
This study presents a Judicial Intersectionality method that incorporates knowledge from arts, humanities, natural sciences, and social sciences. It aims to examine how historical legal, political, and social injustices against Indigenous Australians have persisted in various spheres. When considering the Stolen Generations period, attention is directed on addressing the existing insufficient copyright rights and enhancing future legal results for Indigenous artists. In order to achieve that objective, a unique and distinct copyright system is regarded as the most suitable resolution. Philosophically and pragmatically, this approach was aligned with the Australian Government's 2023 Referendum, which aimed to grant constitutional status to Indigenous individuals and establish a Voice to Parliament advisory council. Although the Referendum did not succeed, the implementation of the standalone sui generis copyright system is a crucial step in the Government's efforts to acknowledge, reconcile, and create a relationship with Indigenous Australians. The Judicial Intersectionality method acknowledges the importance of chance-related connections in unique situations that are uncertain and necessitate action. Given that these circumstances offer fresh starts and chances for transformation, it is now the appropriate moment to embark on this endeavour, to deliberate on the paths of legal modification, and to enact fair, sustainable, and revolutionary copyright reforms for Indigenous Australian artists.